Hyperspectral optical signatures of iron‐limitation in a coastal upwelling system - Sacchidanandan V. Pillai; Yayla Sezginer; Adrian Marchetti; Claire P. Till; Emily V. Speciale; Philippe D. Tortell (Limnology and Oceanography, 2026)
Iron‐limitation within the California Current System drives changes in phytoplankton taxonomic composition and photo‐physiology over a range of spatial scales. Here we demonstrate how these iron‐dependent signatures can be resolved, with high spatial resolution, using continuous ship‐board optical measurements. Deck‐board incubation experiments, along with discrete measurements of iron and macro nutrient concentrations and molecular diagnostic signatures, demonstrated contrasting levels of iron stress across our study region in the northern California Current System during summer, 2023. Photosynthetic pigment measurements indicated that phytoplankton assemblages were largely dominated by diatoms, but low and high iron waters contained differing relative abundances of phytoplankton genera with different mean cell sizes. High frequency ship‐board measurements of hyperspectral particulate absorption demonstrated the presence of two optically distinct phytoplankton assemblages that were associated with varying levels of iron stress. The distribution of the optical clusters across the cruise track showed strong coherence with a number of oceanographic and physiological variables, including phytoplankton size, nutrient drawdown ratios, photosynthetic efficiency () and absorption cross‐section (), and maximum photosynthetic rates. Notably, optical signatures explained more of the observed photo‐physiological variability than other oceanographic variables, such as sea surface temperature and chlorophyll concentration. Variability in phytoplankton iron stress appeared coupled to the age and source of the upwelling water masses. Our results demonstrate the utility of hyperspectral data to map potential iron‐stress with high spatial resolution in dynamic coastal waters.